Strategies to Approach Medicines Litigation: An Action Research Study in Brazil - Machado, Fernanda Lacerda da Silva; dos Santos, Danielle Maria de Souza Serio; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2021)
Background: In the last decades, litigation has been increasingly used to access medicines in Brazil. This phenomenon has led to the development of diverse strategies to reduce its negative impact on the organization of pharmaceutical services. In spite of that, managers still face difficulties dealing with lawsuits. Objective: This study aims to report the planning and implementation of strategies to approach medicines litigation in a municipality located in the southeast region of Brazil. Method: Mixed-methods were employed through an action-research cycle. A network coordination team included researchers from university and municipal managers. The scenario analysis comprised the characterization of pharmaceutical services and the profile of medicines lawsuits. Afterwards, strategies were planned to deal with the central problem identified. The action plan involved educational outreach visits and distribution of printed materials for health professionals, evaluated through opinion survey. Group conversations were conducted with the users of the public health system, followed by thematic analysis of reports. Results: The characterization of pharmaceutical services in the municipality revealed that treatments supplied were in accordance with the National Medicines Policy. In addition, a sector was implemented to attend demands for non-incorporated medicines. In spite of the services available, the characterization of lawsuits indicated that the main claimants were users of the public health system, requiring non-incorporated medicines, with therapeutic alternatives available. Thus, educational outreach visits were held in 14 health units (23 physicians in total). Everyone who answered the evaluation declared that they were very satisfied with the approach. Group conversations with the users of the health system reached 227 participants in total. In regard to users' perception about pharmaceutical services, thematic analysis of reports identified three main categories, including aspects related to medicines provided, users assisted and quality of service. Conclusion: The study described the first cycle of an action-research project to develop strategies to approach medicines litigation at municipal level. The application of educational outreach visits for health professionals and group conversations with health system users are a promising approach to improve access to information about pharmaceutical services in Brazil.